2018
DOI: 10.5812/pedinfect.81349
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara Seroprevalence and Associated Risk Factors Among Ilam Children, West of Iran

Abstract: Background: Human toxocariasis is caused by Toxocara canis and cati, which are the main ascarids of dogs and cats, respectively. Most infected humans are asymptomatic and our understanding of human disease burden is limited by lack of epidemiological studies and insufficient clinical awareness. Objectives: There is no precise report on the seroprevalence of toxocariasis in Ilam children. Therefore, this study found an opportunity to investigate this subject. Methods: In this cross-sectional study, 300 sera of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…The presented study is the first to identify and estimate soil contamination of Toxocara eggs in Ilam. However, studies have been conducted on the prevalence of human toxocariasis among different individuals, including children, pregnant women and diabetic patients in this region [27,28]. The current study describes soil contamination with Toxocara spp.…”
Section: Discussionmentioning
confidence: 95%
“…The presented study is the first to identify and estimate soil contamination of Toxocara eggs in Ilam. However, studies have been conducted on the prevalence of human toxocariasis among different individuals, including children, pregnant women and diabetic patients in this region [27,28]. The current study describes soil contamination with Toxocara spp.…”
Section: Discussionmentioning
confidence: 95%
“…Keeping the dogs at home as a risk factor for human toxocariasis is debatable. Some authors have reported higher rates of infection for those who have been in contact with dogs, while others have found no association between keeping dogs and toxocariasis; however, contact with dogs is important in human infection with toxocariasis ( 14 , 29 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It might have resulted in insufficiency in adopting precautionary measures thus making them more prone to be infected with T. canis. The association of higher disease rates with poor literacy rate and knowledge about diseases is well documented in literature (Castro-Sánchez et al, 2016;Liu et al, 2020;Ullah et al, 2018).…”
Section: Discussionmentioning
confidence: 87%
“…In nomadic populations, this association might be attributed to their poor educational status, poor personal hygiene, and lack of awareness about zoonotic transmission of disease from affected dogs to human beings. Findings of this study revealed a non-significant correlation of seroprevalence of T. canis with exposure to soil and hand washing after exposure to soil.Previously, Fecková et al (2020) andKhoshnood et al (2019) also reported a nonsignificant correlation in Slovakia and the west of Iran, respectively. There are several reports on contamination of soil with eggs of T. canis and prolonged survival of its eggs in soil indicating the exposure to soil as a potential risk determinant for T. canis infection(Papavasilopoulos et al, 2018;Thomas & Jeyathilakan, 2014).Contrary to our findings, Aghamolaie et al (2019), Fouladvand and Barazesh (2020) and Wang et al (2020) reported a significant correlation between contact with soil and T. canis seropositivity in northern Iran, Bushehr Iran, and central China, respectively.…”
mentioning
confidence: 85%
See 1 more Smart Citation